Model and influence factors of oil film thickness in the deformation zone of double cold reduction mill. (8th August 2020) - Li, X. J.; Cui, Y. Y.; He, Z. L.; Bai, Z. H.
ABSTRACT: In the double cold rolling process, oil film thickness in the deformation zone is a key parameter for evaluating rolling lubricity. This study investigated the formation and variation mechanism of oil film thickness on the strip and work roll surface in double cold reduction mill. Subsequently, a calculation model of oil film thickness in the deformation zone of double cold reduction mill was established by combining of the plate out theory and hydrodynamic lubrication principle. Moreover, the influence of emulsion flow, emulsion concentration, emulsion plate out distance, rolling speed, bite angle, entry deformation resistance, back tension, oil initial kinetic viscosity, and oil pressure viscosity coefficient on the oil film thickness were quantitatively analysed. The oil film thickness was achieved with an accuracy greater than 90% through a field application of this calculation model, which provides theoretical foundation for the lubricity control of double cold reduction rolling.